PENERAPAN DEEP LEARNING DENGAN MEDIA PAPAN BACA PINTAR DAN KARTU SUKU KATA UNTUK MENGUATKAN LITERASI KELAS I SD - Nayara Putri Pribadi; Panca Dewi Purwati (STKIP Subang, 2025)
Early literacy skills are essential for first-grade students; however, students at SDN Nongkosawit 2 still demonstrated difficulties in recognizing letter-sound correspondences and reading simple syllables. This study aims to describe the implementation of the Deep Learning approach using the Smart Reading Board and Syllable Cards and to examine their effectiveness in improving students’ early literacy skills. A mixed-method sequential explanatory design was employed, involving 20 first-grade students. Quantitative data were collected through students’ worksheets assessing their ability to combine syllables into words, while qualitative data were obtained through classroom observations and teacher interviews to explain and validate the quantitative findings. The Deep Learning steps included concept introduction, exploration, hands-on experimentation using the media, concept reinforcement, and reflection. The results indicate a significant improvement: the average score increased from 78.8 to 90.1, and learning mastery rose from 45% to 100%. Observations revealed greater student engagement, improved ability to differentiate similar letters, and increased reading confidence. Teacher interviews confirmed that the concrete and manipulative media strengthened students’ understanding of sound–letter–syllable relationships and supported learners with varied abilities. It is concluded that integrating physical media with the Deep Learning approach is effective in enhancing early literacy skills and serves as an accessible, engaging, and adaptive alternative for elementary literacy instruction.